Phase behavior of the orange essential oil/sodium bis(2-ethylhexyl)sulfosuccinate/water system - Feitosa, Eloi [UNESP]; Cavalcante, Vanessa R. O. [UNESP]; Amaral, Lia Q. (Elsevier B.V., 2009)
The ternary phase diagram for the orange essential oil (OEO)/sodium bis(2-ethylhexyl)sulfosuccinate (AOT)/water system was constructed at 25 degrees C. It indicates a large single phase region, comprising an isotropic water-in-oil (W/O) microemulsion (ME) phase (L(2)), a liquid crystal (LC) (lamellar or hexagonal) and a large unstable emulsion phase that separates in two phases of normal and reverse micelles (L(1) and L(2)). In this communication the properties of the ME are investigated by viscosity, electric conductivity and small angle X-ray scattering (SAXS) indicating that the isotropic ME phase exhibits different behaviors depending on composition. At low water content low viscous "dry" surfactant structures are formed, whereas at higher water content higher viscous water droplets are formed. The experimental data allow the determination of the transition from "dry" to the water droplet structures within the L(2) phase. SAXS analyses have also been performed for selected LC samples. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Phase diagram; Microemulsion; AOT; Orange essential oil; Viscosity; Electric conductivity; SAXS